Manufacturing of emulsion type garlic paste: Characterization of rheological properties as affected by lecithin, guar gum, and olive oil using steady, dynamic, and three interval thixotropy tests - Kutlu, Gozde; Baslar, Mehmet; Yilmaz, Mustafa Tahsin; Karaman, Safa; Vardar, Umay-Sevgi; Poyraz-Yildirim, Ecem; Sagdic, Osman (WILEY, 2024)
The objective of this work was to investigate the steady, dynamic mechanical properties, and 3 interval thixotropy test (3 ITT) characterization of emulsion type garlic paste prepared with different concentrations of lecithin, guar gum, and olive oil. A three factor and three level Box Behnken design of response surface methodology was used to specify the physicochemical, steady shear, viscoelastic and deformation and recovery properties (applying 3 ITT) of paste. Garlic paste samples showed non-Newtonian shear thinning behavior and Herchel-Bulkley model was fitted to the data satisfactorily (R-2 > 0.85). Dry matter contents were in the range of 37.13%-41.14% depending on the processing variables. Dynamic mechanical spectrum showed that the garlic paste was weak gel having dominant viscous behavior compared to elastic behavior. Three interval thixrotropy test showed that the samples showed partial recovery after deformation due to the weak gel like character. Optimization showed that the maximum consistency (114.6 Pa s(n)) would be at 2.11 g lecithin, 0.11 g guar gum and 14.96 mL olive oil while the minimum value (49.16 Pa s(n)) would be at 1.02 g lecithin, 0.11 g guar gum, and 5.81 mL olive oil. Overall, the findings of this investigation revealed that the physicochemical and rheological characteristics of garlic paste can be significantly influenced by the concentrations of lecithin, guar gum, and olive oil. It is crucial to carefully select the appropriate concentration levels to achieve the desired quality of garlic paste.
Keywords: 3-ITT; dynamic rheology; garlic paste; optimization; STORAGE CHARACTERISTICS; O/W EMULSIONS; HYDROCOLLOIDS; STABILITY; KINETICS; BEHAVIOR; XANTHAN; FRUIT; PUREE; Engineering; Food Science & Technology